2009
DOI: 10.1123/jpah.6.2.137
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Media Exposure and Its Association With Activity-Related Outcomes in Female Adolescents: Cross-Sectional and Longitudinal Analyses

Abstract: . Electronic media exposure and its association with activity-related outcomes in female adolescents: Cross-sectional and longitudinal analyses. Journal of Physical Activity and Health, 6(2) Activity and Health, 2009, 6, 137-143 © 2009 Human Kinetics, Inc. Background: Few investigations have assessed in adolescent girls the cross-sectional and longitudinal associations between elevated exposure to electronic media (EM) and activityrelated outcomes such as compliance with physical activity (PA) standards o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
26
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 37 publications
0
26
0
4
Order By: Relevance
“…Several previous studies have also examined the associations between sedentariness and CRF 18 19 3436. However, most of them have used subjective measures of sedentariness such as television viewing, computer use or screen time (television+computer).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have also examined the associations between sedentariness and CRF 18 19 3436. However, most of them have used subjective measures of sedentariness such as television viewing, computer use or screen time (television+computer).…”
Section: Discussionmentioning
confidence: 99%
“…Sedentary activities have been defined as “activities that do not increase energy expenditure substantially above the resting level”, that is, activities that involve energy expenditure of <1.5 metabolic equivalents,17 such as lying down, sitting and watching television. Overall, previous studies defined sedentary behaviours as time in screen time (television+computer) to examine the associations between sedentariness and CRF 18 19. Nevertheless, these sedentary behaviours are far from capturing the total amount of everyday sedentary time in both adults and young people 20 21.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has illustrated that decreased physical activity is associated with more time spent on the internet [7,8]. Higher levels of media exposure in general have been associated with less time doing vigorous physical activity [9]. Conversely, another study found little relationship between time spent on the internet and fitness [10].…”
Section: Introductionmentioning
confidence: 98%
“…Otro mecanismo sugiere que el comportamiento sedentario puede estar mediando la asociación. Es sabido que el sedentarismo está asociado a una mayor ingesta calórica (56), al tiempo que desplaza el tiempo para la realización de actividad física (57), conduciendo a una reducción de la CCR (8,58), y a un incremento de la adiposidad (59). La composición genética es otro mecanismo propuesto, sugiere que la composición genética explica en parte la asociación entre adiposidad excesiva y baja CCR, y se basa en la presencia de un polimorfismo genético para adiposidad y capacidad física, de hecho, ya se han encontrado genes relacionados con la CCR (60) y con la adiposidad en exceso (61).…”
Section: Discussionunclassified